Telemedical Support for Military Medicine. Issue 11 (22nd June 2018) - Nettesheim, Neal; Powell, Doug; Vasios, William; Mbuthia, Jennifer; Davis, Konrad; Yourk, Dan; Waibel, Kirk; Kral, Daniel; McVeigh, Francis; Pamplin, Jeremy C
Absract: Introduction: U.S. military forces have engaged in combat in mature areas of operations (AOs) in Iraq and Afghanistan that allow for casualty evacuation to definitive surgical care within "The Golden Hour." Future combat casualty care will be complex and challenging. Facing the medical demand of the Multi-Domain Battlefield remains an uncertain problem set. What can be anticipated is that a near peer adversary will not allow freedom of movement, air superiority, or uninterrupted communications. Telemedicine is one solution that can aid in this environment because it can reduce the medical footprint in a theater of operation by bringing the remote expert's knowledge and experience to the point of need. Materials and methods: Telemedicine can augment the capabilities of caregivers in austere, operational settings using synchronous or asynchronous technology to optimize the care of casualties who are delayed in evacuation to higher levels of care. These technologies have been implemented and tested over the past 30 yr. We reviewed the historical literature about military telemedicine and assembled current leaders in military telemedicine to write this review. Results: This manuscript reviews the history of and current capabilities of military telemedicine. Conclusions: Broad implementation of telemedicine in the operational setting is challenged by network limitations and cyber security concerns. Reliable, high bandwidth, low latency, secure communications that is necessary for advanced telemedicine capabilities (i.e., procedural telementoring) will not likely be available at all times during future engagements. The military must develop and train a full spectrum of telemedical support options that include low-to-high bandwidth solutions. Telemedicine is not a substitute for deploying anticipated medical resources or optimizing training: telemedicine is plan B where plan A is training, deployment, and casualty evacuation. Nevertheless, when network and communications resources are sufficient, telemedicine brings advanced expertise to austere, resource-limited contexts when timely evacuation is not possible.